2017
DOI: 10.3174/ajnr.a5370
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Diffusion Coefficient Histograms of Human Papillomavirus–Positive and Human Papillomavirus–Negative Head and Neck Squamous Cell Carcinoma: Assessment of Tumor Heterogeneity and Comparison with Histopathology

Abstract: BACKGROUND AND PURPOSE:Head and neck squamous cell carcinoma associated with human papillomavirus infection represents a distinct tumor entity. We hypothesized that diffusion phenotypes based on the histogram analysis of ADC values reflect distinct degrees of tumor heterogeneity in human papillomavirus-positive and human papillomavirus-negative head and neck squamous cell carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
83
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 27 publications
(51 reference statements)
7
83
0
Order By: Relevance
“…HPV-negative tumors were correlated with high ADC-values (r = 0.452). This is in line with some previous studies [28,[33][34][35], in which higher ADC histogram parameters in HPV-negative patients were found. This was confirmed by Meyer et al [36], who found a negative correlation of high ADC max and ADC SD with low P53 expression in HPVnegative tumors, which lead to minimal cell cycle arrest, senescence or apoptosis [37].…”
Section: Tablesupporting
confidence: 93%
See 1 more Smart Citation
“…HPV-negative tumors were correlated with high ADC-values (r = 0.452). This is in line with some previous studies [28,[33][34][35], in which higher ADC histogram parameters in HPV-negative patients were found. This was confirmed by Meyer et al [36], who found a negative correlation of high ADC max and ADC SD with low P53 expression in HPVnegative tumors, which lead to minimal cell cycle arrest, senescence or apoptosis [37].…”
Section: Tablesupporting
confidence: 93%
“…This was confirmed by Meyer et al [36], who found a negative correlation of high ADC max and ADC SD with low P53 expression in HPVnegative tumors, which lead to minimal cell cycle arrest, senescence or apoptosis [37]. This was attributed to a more keratinizing morphology with variable cellularity, cell shape, keratin pearls, large intratumoral necrosis, hemorrhage and stromal cells found in HPV-negative tumors [28,31,33]. However, 2 studies did not find any differences of ADC histogram parameters between p16 status [36] or between the more accurate HPV status [15].…”
Section: Tablementioning
confidence: 71%
“…First, the HPV status of the patients showed no significant results on prognosis, which maybe due to small number of known HPV status. As many previous studies insisted that HPV status is an important factor for prognosis [ 35 ] and could affect the SUV [ 36 ] and ADC [ 37 ] measurements, it needs to be further studied with combined PET/MRI parameters in the future. In addition, SUV threshold for metabolo-volumetric parameters (MTV and TLG) is not clearly defined yet [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This postprocessing tool can be applied retrospectively to all images acquired in clinical routine. 26,27 However, lack of standardized software, evolving research, and variable numeric algorithms currently limit the use of these new promising tools in clinical routine.…”
Section: Discussionmentioning
confidence: 99%